Democratic Republic of the Congo : Third Review of the Three-Year Arrangement Under the Extended Credit Facility, Financing Assurances Review, and Request for Modification of Performance Criteria: Staff Report and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Satisfactory policy implementation continues in the program under challenging conditions, but the uncertain economic, social, and political environment will test this commitment. The program is flexible to accommodate a partial pass-through of higher world oil prices to domestic fuel prices and further pro-poor spending, but ongoing fiscal discipline will be essential to achieve the program's fiscal objectives. The implementation of revenue-enhancing measures will require political will. Executive Directors welcome the efforts to implement the broad range of reforms in extractive industries.